Consumer voice towards environmental green mobile phone : A case of Universiti Teknologi Malaysia Students - Takhmina, Makhkamova (2014)
Rapid growing of electronic products waste such as mobile phone has become a main issue of waste stream in Malaysia. This can be explained by the fact that current process of product development is lack of consumer voice which led to poor eco-design of the green product in the marketplace. Therefore, this study aimed to investigate consumer concerns and considerations towards environmental green mobile phone which will better address consumer perspectives in the planning stage of product development. This study applied quantitative methods of investigating consumer voice for green definition of the mobile phone as well as main criteria that affect consumer choice and consumer priority criteria for mobile phone green design idea. To achieve assigned objectives, this study used exploratory Factor Analysis and Analytic Hierarchy Process to determine priority of criteria for mobile phone green design idea. The findings of the study revealed that consumer defined green mobile phone, that produce the least amount of pollution and consumes the least amount of energy and resources. Furthermore, consumer selected priority criteria is green mobile phone that has higher quality with innovative features and it is considerably safe to the living environment, with energy efficiency and resource efficiency features but with considerably lower price. The implication of this study proposed an approach of eliciting consumer voice in the planning stage of the product development which assist designer to take into account consumer voice for environmental green mobile phone eco-design development. The results of the study recommended further research in exploration of consumer perspective in design for recycling, design for waste reduction as well as design for reuse by using the proposed approach